(untitled) (Swiss Medical Weekly, 2015)
Arthritis encompasses a heterogeneous group of diseases characterised by inflammation that leads not only to joint damage, bone erosion, severe pain and disability, but also affects other organs of the body, resulting in increased morbidity and mortality. Although the mechanisms underlying the pathogenesis of joint diseases are for the most part unknown, a number of nutrient and non-nutrient components of food have been shown to affect the inflammatory process and, in particular, to influence clinical disease progression. The Mediterranean diet model has already been linked to a number of beneficial health effects: both fat and non-fat components of the Mediterranean dietary pattern have been shown to exert important anti-inflammatory activities by affecting the arachidonic acid cascade, the expression of some proinflammatory genes, and the activity of immune cells. N-3 polyunsaturated fatty acids, in particular, have been shown to affect lymphocyte and monocyte functions, crucially involved in adaptive and innate immunity. Although some aspects concerning the mechanisms of action through which the Mediterranean diet pattern exerts its beneficial effects remain to be elucidated, arthritis patients may potentially benefit from it in view of their increased cardiovascular risk and the treatment they require which may have side effects.